Plant dominance in a subalpine montane meadow: biotic vs. abiotic controls of subordinate diversity within and across sites - Erika LaPlante; Lara Souza (PeerJ, 2018)
Background Understanding the underlying factors that determine the relative abundance of plant species is critical to predict both biodiversity and ecosystem function. Biotic and abiotic factors can shape the distribution and the relative abundance of species across natural communities, greatly influencing local biodiversity. Methods Using a combination of an observational study and a five-year plant removal experiment we: (1) documented how plant diversity and composition of montane meadow assemblages vary along a plant dominance gradient using an observational study; (2) tracked above- and belowground functional traits of co-dominant plant species Potentilla and Festuca along a plant dominance gradient in an observational study; (3) determined whether plant species diversity and composition was directly influenced by commonly occurring species Potentilla and Festuca with the use of a randomized plot design, 5-year plant removal experiment (no removal control, Potentilla removed, Festuca removed, n = 10). Results We found that subordinate species diversity and compositional dissimilarity were greatest in Potentilla and Festuca co-dominated sites, where neither Potentilla nor Festuca dominated, rather than at sites where either species became dominant. Further, while above- and belowground plant functional traits varied along a dominance gradient, they did so in a way that inconsistently predicted plant species relative abundance. Also, neither variation in plant functional traits of Festuca and Potentilla nor variation in resources and conditions (such as soil nitrogen and temperature) explained our subordinate diversity patterns. Finally, neither Potentilla nor Festuca influenced subordinate diversity or composition when we directly tested for their impacts in a plant removal experiment. Discussion Taken together, patterns of subordinate diversity and composition were likely driven by abiotic factors rather than biotic interactions. As a result, the role of abiotic factors influencing local-level species interactions can be just as important as biotic interactions themselves in structuring plant communities.